Implementation of features of the officialese (legal) style in the Code of Canon Law (selected issues) - Wojtak, Maria (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The subject of the analysis in this article is the Code of Canon Law (of 1987). Generally all features of the officialese (legal) style and their exponents known from secular communication have been implemented in this document. The Code is distinguished by a special composition, i.e. a division into segments, ways of naming the segments and their arrangements. Standardization as a feature of the style is enriched by exponents implemented in a microscale, and so, first of all, the navigation formulas, contributing to cohesion of the utterance and being a manifestation of a pursuit of precision. The author sees the exponents of this feature in formulas defining the scope of norms and also clarifying the content of provisions. Yet, legal definitions are the most important manner of specyfying the content of legal concepts (terms). The Code of Canon Law contains a few schemata of such definitions, which strengthens and emphasizes the triteness of the wording. The ways of formulating the directives are also in conformity with the law, they also become the exponents of impersonality as a feature of the officialese. Wheareas manifestations of interference with the religious style are included in the content of the norms. The abovementioned features, occuring in the complementary relations, contribute to create a set of exponents of the genre style of a legal utterance which is a code.